Handmade clay bricks: chemical, physical and mechanical properties - Lourenço, Paulo B. (2010)
The clay brick masonry that is much used in historical structures often is in a rather poor state of conservation. In order to intervene correctly in these buildings, it is convenient to characterize the old material. For this purpose, a large sample of clay brick specimens from the 12th to 19th century were collected from six Portuguese monasteries, and were characterized chemically, physically and mechanically. A large variability of the properties was found. Additionally, a sample of handmade new bricks, which are commonly used as replacing material, was also analysed. The results were compared to the old bricks and could be possibly adequate as substitution bricks. Still, significant differences were found in chemical composition, and in water absorption and porosity, which are much lower in modern handmade bricks. With respect to mechanical properties, the range of values found in old bricks was rather high and the degree of deterioration exhibited a large scatter, meaning that a conclusion is hardly possible.